Nanofluid as an Alternative Coolant in Machining: A Review - K., Kadirgama (Akademia Baru Publishing (M) Sdn Bhd, 2020)
This review paper is concerned about the important of nanofluid in machining. It is discussed in several parts such as cutting force, surface roughness, tool life and tool wear. Various type of nanofluid is discussed in this paper with an effect on the surface roughness, force, tool life, and wear. Nanofluid plays a significant role in the increment of tool life and reducing tool wear. Nanofluid creates an artificial layer on top of the workpiece, and this reduces wear at the cutting tool. It seems that nanofluid can be the next alternative coolant in machining.